2010
DOI: 10.1016/j.jneuroim.2010.06.016
|View full text |Cite
|
Sign up to set email alerts
|

A unique antibody gene signature is prevalent in the central nervous system of patients with multiple sclerosis

Abstract: B cells isolated from the CSF of patients with multiple sclerosis (MS) have a unique accumulation of somatic hypermutation, within the B cell receptor, termed the antibody gene signature (AGS). The focus of this study was to investigate whether the AGS could also be detected in MS brain tissue. Genetic analysis of B cells isolated from post-mortem CNS tissue samples from four MS brains demonstrated that signature enriched B cells are present at the site of tissue injury as well as in the circulating CSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The IGHV transcriptome in CSF of MS patients did, however, to a larger extent reflect intrathecal synthesis of IgG, and was characterized by more pronounced affinity maturation and selective use of IGHV4 genes. It has previously been reported that IGHV transcripts recovered from CSF and CNS B cells of MS patients have undergone somatic hypermutation [16,22,23,[33][34][35], have biased IGHV gene usage [15,20], match CSF IgG [19,21], and communicate across the blood-brain barrier [20,21,23,35]. The sequencing depth achieved using Illumina technology, combined with mass-spectrometric verification, allowed us to extend these findings by showing that all examined MS patients, regardless of disease duration and therapy, had closely related IGH-VDJ transcripts on both sides of the blood-CSF barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The IGHV transcriptome in CSF of MS patients did, however, to a larger extent reflect intrathecal synthesis of IgG, and was characterized by more pronounced affinity maturation and selective use of IGHV4 genes. It has previously been reported that IGHV transcripts recovered from CSF and CNS B cells of MS patients have undergone somatic hypermutation [16,22,23,[33][34][35], have biased IGHV gene usage [15,20], match CSF IgG [19,21], and communicate across the blood-brain barrier [20,21,23,35]. The sequencing depth achieved using Illumina technology, combined with mass-spectrometric verification, allowed us to extend these findings by showing that all examined MS patients, regardless of disease duration and therapy, had closely related IGH-VDJ transcripts on both sides of the blood-CSF barrier.…”
Section: Discussionmentioning
confidence: 99%
“…77 Sequences were analyzed and compiled into databases containing VH gene, JH gene, CDR3 amino-acid sequence and mutation information using a Perl program developed at UTSWMC 78 that utilizes the IMGT/V-QUEST tool as a basis for extracting the sequence information. Sequences with o85% homology to their VH germline gene segment were dismissed to avoid introducing potential VH gene miscalls into the databases.…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, each patient has a unique pattern “OCB fingerprint” of CSF immunoglobulins [ 20 , 21 ]. This biological signature may be scored according to the typical positions of mutational replacements (hotspots) on IgG and can be used as a composite signature Z -score, which is highly predictive of the conversion of clinically isolated syndromes (CIS) to clinically defined MS [ 22 , 23 ]. These hotspot codons reside in the complementary determining region (CDR) where they are predicted to have contact with the (unknown) antigen(s).…”
Section: Pathway Of Intrathecal Igg Synthesismentioning
confidence: 99%